Distribution Mapping of Smaller Arachnid Orders and Pseudoscorpiones in Malaysia - Faris Adly; Dzulhelmi Muhammad Nasir; Nur-Athirah Abdullah; Suriyanti Su; Nurul Fatihah Abd Latip; Madihah Halim; Faszly Rahim (Entomological Society of Indonesia in collaboration with the Department of Plant Protection, Faculty of Agriculture, 2024)
Vol. 19 No. 2